Comparative characteristics of histomorphometric changes in rat testicles after injection of a sclerosant into the cavum vaginale and simulation of operations for hydrocele. - Kvyatkovskaya , T.O.; Kvyatkovsky , E.A.; Nefodova , O.O.; Kryzhanovsky, I.D.; Tereshchenko, N.M.; Hruzd , V.V. (Морфологія / Morphologia / Morfologìâ, 2022)
Background. Hydrocele affects up to 1% of men and is associated with impaired testicular function and impaired spermatogenesis. Treatment of hydrocele is mainly operative - hydrocelectomy. Sclerotherapy is gaining more acceptance for the treatment of hydrocele due to its less invasive nature and faster patient recovery. Objective. The aim is to determine the changes in the histomorphometric parameters of the testicles of rats after simulating surgical interventions and sclerotherapy used for hydrocele. Methods. The study of histomorphometric changes in testicles of rats after simulation of surgical treatment of hydrocele and sclerotherapy was carried out on 48 white laboratory sexually mature male rats with an observation period of 30 days. The ratio of the spermatogenic epithelium, the lumen of the convoluted seminiferous tubules and interstitial tissue, the percentage of sections of the convoluted seminiferous tubules with the absence of spermatozoa and late spermatids, and the transverse size of the convoluted seminiferous tubules were determined. Results. Fenestration of testicular membranes was accompanied by the smallest histomorphometric changes in their parenchyma. Lord's operation, although positioned as gentle, led to changes in the convoluted seminiferous tubules, which was expressed in slowing down the maturation of spermatids. After the Bergmann operation, almost all histomorphometric parameters were slightly worse than after the Winckelmann operation, but these differences were not statistically confirmed. After sclerosing the testicles with the introduction of 1% and 3% ethoxysclerol into the vaginal cavity of the testicle, the results of histomorphometry were close to the results after Bergmann and Winkelmann operations. However, after sclerotherapy with ethoxysclerol, the percentage of tortuous seminiferous tubules with no spermatozoa and late spermatids was significantly worse than after all surgical methods studied. Conclusion. After sclerotherapy with ethoxysclerol, the results of histomorphometry of the testicles were similar to the results of hydrocelectomy according to most indicators, but significantly worse in terms of sperm maturation. No significant difference was observed between the 1% and 3% ethoxysclerol groups. Therefore, we believe that sclerotherapy with ethoxysclerol should be used in the absence of relevance of the fertility function.